Development of Diagnostic Test Instruments as Placement Tests to Determine Students’ Cognitive Learning Levels on Acid-Base Material - Saifatun Nur Hafidzah Fida; Rinaningsih Rinaningsih (Journal of Educational Chemistry (JEC), 2025)
This study aims to determine the validity and discriminatory power of diagnostic test instruments as placement tests on acid-base material and to determine the level of students' cognitive learning. This diagnostic test instrument development research refers to the Research & Development (R&D) development method. Data collection in this study used tests, interviews, and questionnaires. The research stage begins with potential problems, data collection, product design stage, development of diagnostic test instruments and validation by experts, validity tests, difficulty level tests, and discriminatory power tests on small-scale tests and interpretation of students' cognitive levels on large-scale trials. The results of the assessment by expert validators showed that the criteria for the developed instrument were valid. The results of the analysis of the validity of the test items obtained 25 valid question items. The results of the test of the level of difficulty of the questions obtained 11 easy criteria questions and 14 medium criteria questions. The results of the discriminatory power test obtained 25 question items with very good discriminatory power. The results of the large-scale trial showed that the average interpretation of the results of the diagnostic test instrument was 78.81%. The percentage of students who passed the test was 70.3% while the percentage of students who failed was 30%. This shows that the diagnostic test instrument is effective in that it can improve students' understanding of acid-base chemistry material.